Effects of a band application of polyolefin-coated diammonium phosphate on the nutritional quality of rhubarb and Swiss chard - Ombódi, A.; Saigusa, M. (International Journal of Horticultural Science, 2000)
Dietary intake of large amounts of nitrates and oxalates presents a health hazard. In this study experiments were conducted with two oxalate accumulating vegetables rhubarb (Rheum rhabarbarum L.) and Swiss chard (Beta vulgaris L. var. cicla L.)) using POC-DAP in order to improve their nutritional quality. In the rhubarb experiment oxalate content was significantly reduced by band application of POC-DAP, while effects on ascorbate and nitrate contents were ambiguous. The improved nutritional quality in the POC-DAP treatment was rather a cause of ammonium nutrition than a cause of less amount of released fertilizer nitrogen. In the Swiss chard experiment oxalate and nitrate contents were reduced, while ascorbate content was increased by a band application of POC-DAP. The improved nutritional quality in the POC-DAP treatment was the cause of both the less amount of released nitrogen and the realised ammonium nutrition. It was also found that by using POC-DAP for Swiss chard cultivation, labour and energy costs of top-dressings could be eliminated without yield decrease. It was concluded that the nutritional quality of rhubarb and Swiss chard could be improved by using a band application of POCDAP.